1924
DOI: 10.1002/cber.19240570725
|View full text |Cite
|
Sign up to set email alerts
|

Nitrierungsprodukte des γ‐Amino‐pyridins

Abstract: Ruf Grund der Resultate von K o e n i g s , K i n n e und WeiB1) hielten wir das von ihnen beschriebene p r i m l r e N i t r i e r u n g s p r o d u k t d e s y -Am i n op y r i d i n s fur das p -K i ta. o d e r i v a t dieses Stoffes. Wir beabsichtigten, die Arninogruppe desselben gegen Hydroxyl auszutauschen, um weifer iiber ein Chlor-nitro-pyridin zu neuen Derivaten zu kommen. Alle unsere Versuche, durch Alkalieinwirkuhg oder Diazotierung ein Oxy-nitm-Derivat zu erhalten, schlugen naturgemlB fehl, da wir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

1960
1960
1985
1985

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 4 publications
0
6
0
3
Order By: Relevance
“…With PNMT and HMT the inhibition constants for 3-deaza-SAH (2) were of similar magnitude to those found for COMT (Table II) and were within the same order of magnitude as that for SAH, indicating that the nitrogen in the 3 position of SAH is not an absolute requirement in binding to these enzymes. For HIOMT, the Kis for 3deaza-SAH was about 12 times greater than that for SAH, further illustrating the high specificity of this enzyme for the structural features of SAH. With all of the enzymes studied the methylated derivatives 1 and 3 had inhibition constants 10-100 times greater than that for SAH, again indicating the importance of the 6-amino group in binding.…”
Section: Methodsmentioning
confidence: 90%
“…With PNMT and HMT the inhibition constants for 3-deaza-SAH (2) were of similar magnitude to those found for COMT (Table II) and were within the same order of magnitude as that for SAH, indicating that the nitrogen in the 3 position of SAH is not an absolute requirement in binding to these enzymes. For HIOMT, the Kis for 3deaza-SAH was about 12 times greater than that for SAH, further illustrating the high specificity of this enzyme for the structural features of SAH. With all of the enzymes studied the methylated derivatives 1 and 3 had inhibition constants 10-100 times greater than that for SAH, again indicating the importance of the 6-amino group in binding.…”
Section: Methodsmentioning
confidence: 90%
“…Our procedure for synthesis of 3-deaza-C-Ado (4) involved condensation of 4-chloro-3-nitropyridine24 ( 14) with (±)-4/3-amino-2a,3a-dihydroxy-ld-cyclopentanemethanol ( 13)21 (Scheme II). The reaction product 15 was reductively chlorinated to 16 with stannous chloride in hot 12 N HC1 following the general procedure of Koenig et al 25 The NMR spectra showed a coupling constant between H-5 and H-6 equal to 6 Hz, which is consistent with the assigned structure. Koenig et al 25 had reductively chlorinated 3-nitro-4-aminopyridine to give what was thought to be 3,4-diamino-6-chloropyridine, but the product was later shown by Mizuno et al26 to be 3,4-diamino-2chloropyridine.…”
Section: Resultsmentioning
confidence: 58%
“…1.80 (siklohekzan halkasının metilen protonları 10 H, m), 3.05 (siklohekzan halkasının metin protonu, 1 H, m), 7.36 (6. konumdaki proton, 1 H, k), 8.07 (7. ppm. 1.00 (n-propil zincirinin metil proton ları, 3 H, t), 1.90 (n-propil zincirinin 2. konumundaki metilen protonları, 2 H, seks.…”
Section: Spektrumuunclassified
“…1.00 (n-propil zincirinin metil proton ları, 3 H, t), 1.90 (n-propil zincirinin 2. konumundaki metilen protonları, 2 H, seks. ), 3.05 (n-propil zincirinin 1. konumundaki meti len protonları, 2 H, t), 8.13 (7. …”
Section: Spektrumuunclassified
See 1 more Smart Citation